PENERAPAN METODE EXPONENTIALLY WEIGHTED MOVING AVERAGE (EWMA) DAN METODE SEMI VARIANS (SV) DALAM PERHITUNGAN RISIKO PORTOFOLIO SAHAM OPTIMAL - Rachman, Faizal (2014)
Purpose of this study is to calculate the value of the optimal stock portfolio risk. Method used in this research in determining the risk value (Value at Risk) are Exponentially Weighted Moving Average (EWMA) and Semi-Variance (SV). EWMA model is chosen because the data of share value return tend to be heteroskedastis while SV is chosen because it does not require any distribution assumption so that both methods can be applied to the same share value return data. With this stud, the investor will make trades can determine which method is most appropriate in order to minimize the risk of loss so as to obtain the maximum benefit. With this study, the investors who will make trades can determine the most appropriate method in order to minimize the risk of loss so that they obtain the maximum benefit. The results showed that the optimal portfolio that was obtained using EWMA method has a portfolio composition consisting INDF 43,15%, UNVR 21,58%, SMGR 22,35%, INTP 12,92%, with the level of risk (VaR) of Rp 9.910.339,867 or 2,47%. While using the SV, it was obtained INDF 38,09%, UNVR 24,85%, SMGR 19,53%, INTP 17.53% ,with the level of risk (VaR) of Rp 9.448.912,9 or 2,35%. This study uses the exposure value of Rp 100 million for each of its shares, or Rp 400 million for the portfolio.